2022
DOI: 10.3390/nu14163272
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of a Multifaceted Intervention on Dietary Quality in Schoolchildren and the Mediating Effect of Dietary Quality between Intervention and Changes in Adiposity Indicators: A Cluster Randomized Controlled Trial

Abstract: Some studies have found associations between dietary quality and obesity and their concurrent changes were observed in a few interventions. The present study aimed to assess the effect of a multifaceted intervention for childhood obesity on dietary quality and examine the mediating effect of dietary quality between the intervention and changes in adiposity indicators. Based on the social ecological model, the cluster randomized controlled trial included five components (three targeted children and two targeted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
(53 reference statements)
0
1
0
Order By: Relevance
“…A review of evidence from intervention studies confirmed the view that physical frailty is a reversible condition through lifestyle changes [4]. However, the majority of dietary interventions to reverse or delay onset or progression of physical frailty were conducted in frail and pre-frail community-dwelling older adults, those in hospital or in long term institutional care, or those with chronic conditions such as type 2 diabetes [4][5][6][7][8][9]. Hence, it is crucial to demonstrate associations of overall dietary patterns and physical frailty in community-dwelling adults who are not yet frail or pre-frail, in order to establish evidence for frailty prevention later in life in the general population.…”
Section: Introductionmentioning
confidence: 99%
“…A review of evidence from intervention studies confirmed the view that physical frailty is a reversible condition through lifestyle changes [4]. However, the majority of dietary interventions to reverse or delay onset or progression of physical frailty were conducted in frail and pre-frail community-dwelling older adults, those in hospital or in long term institutional care, or those with chronic conditions such as type 2 diabetes [4][5][6][7][8][9]. Hence, it is crucial to demonstrate associations of overall dietary patterns and physical frailty in community-dwelling adults who are not yet frail or pre-frail, in order to establish evidence for frailty prevention later in life in the general population.…”
Section: Introductionmentioning
confidence: 99%